Urban livelihoods and labor markets - de Haan, Arjan (International Food Policy Research Institute, 2000)
Urbanization is increasingly accompanied by globalization through trade and financial liberalization, both of which reinforce the importance of cities and economies of scale. Urban labor markets in 2020 are likely to become even more competitive and flexible. To take advantage of open, expanded, but highly competitive markets, governments need to react rapidly to demands imposed by a global labor market and now rely less on inward-oriented development policies... Policies should promote access of the poor to financial capital through microfinance schemes; build the capabilities of the urban poor through formal education and training so that they can secure high-quality employment; and take into account the heterogeneity of labor markets and fluctuating nature of labor supply and demand. Governments may also need to pursue special policies to reduce gender disparities and to break through the labor market segmentation that inhibits certain groups from taking up jobs in more rewarding activities. -- from Text